Soil Organic Carbon Stocks and Spatial Variability in Urban Green Spaces: Insights from the Kalyan–Dombivli Municipal Corporation, Mumbai Metropolitan Region, India - Madhuri Wani; D.M. Mahajan; Deepavali Shirurkar (Journal of the Indian Society of Soil Science, 2026)
within the Kalyan–Dombivli Municipal Corporation (KDMC) in the Mumbai Metropolitan Region, India. A total of 102 composite soil samples were collected from 30 ward groups representing residential, agricultural, and mixed land-use zones at two depths (0–15 cm and 15–30 cm). Laboratory and geospatial analyses quantified SOC distribution, depth-wise variation, and land-use influence. Results revealed high mean SOC concentrations (≈10.9%) and substantial average carbon stocks ( 404 t C ha-1 within 0–30 cm). Surface soils exhibited slightly higher SOC than sub-surface layers, though the latter contributed nearly half of the total carbon pool, indicating deep carbon stabilization. Spatial mapping identified distinct carbon “hotspots” (>450 t C ha-1) in vegetated residential and institutional areas such as Kala Lake and Titwala, whereas disturbed and compacted peri-urban zones recorded lower stocks (<250 t C ha-1). Despite moderate variation across land-use categories, sustained vegetation cover emerged as the dominant factor influencing SOC accumulation. These findings underscore that tropical urban soils, when managed ecologically, function as effective carbon sinks comparable to natural ecosystems. The study provides a scientific foundation for integrating soil carbon management into municipal climate strategies, emphasizing the role of urban green spaces in carbon neutrality, climate adaptation, and sustainable city planning.